2020
DOI: 10.1002/ejsp.2680
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of enactment and concealment for felt authenticity: Understanding the effects of stigma through self‐distancing and motive fulfillment

Abstract: Who am I? While the quality of answers to this question will vary from person to person, most can provide several answers with ease. These answers represent the elements comprising a person's subjective identity structure, reflecting their values, goals, traits, characteristics, preferences, social collectives and categories, and relationships and roles (Vignoles, 2011). Subsumed within this simple question is another, more complex one: "How do I know that who I say I am is truly me?" The question is not merel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…An important reason why moving the self away from a stigmatized ingroup has negative consequences for individuals' health and well-being is that it thwarts identity-specific motives, such as self-esteem, belonging, and efficacy, and in turn negatively affects felt authenticity (Crabtree & Pillow, 2020, this issue; see also Dormanen et al, 2020). Not being able to be your true self because of a discriminatory context takes its toll, psychologically and physically.…”
Section: Consequences For the Individualmentioning
confidence: 99%
“…An important reason why moving the self away from a stigmatized ingroup has negative consequences for individuals' health and well-being is that it thwarts identity-specific motives, such as self-esteem, belonging, and efficacy, and in turn negatively affects felt authenticity (Crabtree & Pillow, 2020, this issue; see also Dormanen et al, 2020). Not being able to be your true self because of a discriminatory context takes its toll, psychologically and physically.…”
Section: Consequences For the Individualmentioning
confidence: 99%
“…This study makes three contributions to the literature. First, it extends the pertinent literature that relied on data collected cross-sectionally (e.g., Brownfield & Brown, 2020; Mereish et al, 2017; Mereish & Poteat, 2015; Petrocchi et al, 2020; Riggle et al, 2017) or over a short time period (e.g., Crabtree & Pillow, 2020; Fletcher & Everly, 2021; Giano et al, 2019; Kiekens & Mereish, 2021). The two-wave data collected over a 1-year period strengthen our ability to make inferences about the directionality of the relationships among the variables and explore the longer term effects of sexual orientation concealment.…”
Section: The Mechanisms Of Sexual Orientation Concealmentmentioning
confidence: 69%
“…Many researchers have found that living in an authentic manner is the key to personal and social wellness (Fletcher & Everly, 2021; Jourard, 1971; Lynch et al, 2009; Petrocchi et al, 2020) because authenticity allows others to know the individual’s true self and enables reciprocal and open interactions (Kernis & Goldman, 2006; Pachankis, 2007). Conversely, concealing a stigmatized identity has been found to threaten the sense of authenticity (Crabtree & Pillow, 2020; Follmer et al, 2020). A meta-analysis of 75 studies reveals a strong positive correlation between authenticity and well-being (Sutton, 2020).…”
Section: The Mechanisms Of Sexual Orientation Concealmentmentioning
confidence: 99%
“…Being open and honest has been associated with a feeling of increased authenticity and opportunities to experience validation from others. Recent research (Crabtree & Pillow, 2020) suggests that lack of felt authenticity is more a product of self‐distancing strategies than the existence of a stigmatised identity. However, the experience of those interviewed in this study was that visible psychosis, or lack of concealment, often resulted in strong emotional reactions from others in existing social networks and feelings of rejection:
I can't really go back to my old friendship group because they're all (2.0) sort of weirded out by what happened, there's all these sort of pre‐ sort of like (.)
…”
Section: Resultsmentioning
confidence: 99%